2019
DOI: 10.1037/spq0000308
|View full text |Cite
|
Sign up to set email alerts
|

Linking social and emotional learning standards to the WCSD Social–Emotional Competency Assessment: A Rasch approach.

Abstract: Growing interest in understanding the role of students' social-emotional competence for school success necessitates valid measures for large-scale use. We provide validity evidence for the 40-item Washoe County School District Social-Emotional Competency Assessment (WCSD-SECA), a student self-report measure that came from a researcher-practitioner partnership. The WCSD's social and emotional learning standards, which detail when and at what grade students are expected to express different competencies, contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…Researchers and practitioners also need to bear in mind that the four constructs we examine are not necessarily defined the same way by surveys used outside of CORE, and that items might therefore look quite different (e.g., Crowder et al, 2019). More concretely, most students outside California do not take the CORE surveys and the CORE surveys differ from those used in other districts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers and practitioners also need to bear in mind that the four constructs we examine are not necessarily defined the same way by surveys used outside of CORE, and that items might therefore look quite different (e.g., Crowder et al, 2019). More concretely, most students outside California do not take the CORE surveys and the CORE surveys differ from those used in other districts.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of arguments for and against self-report measures, they are used widely by developmental and educational researchers, due in part to their ease of administration (Crowder et al, 2019). In fact, most of what we know about how students develop SE skills almost certainly comes from self-report measures.…”
Section: General Evidence On Uses Of Selfreport Measuresmentioning
confidence: 99%
“…However, despite the presence of small to moderate DIF based on the change in R2 and % Δβ1, all DIF was classified as negligible, and Lambert et al (2018) concluded that DIF did not have a significant impact on test scores. Crowder et al (2019) evaluated DIF between White and Hispanic/Latinx students on a 40-item social–emotional competency assessment that included four items related to self-management of goals. In their sample of over 13,000 students in grades 5, 6, 8, and 11, no DIF was flagged on those four goal-related items.…”
Section: Discussionmentioning
confidence: 99%
“…These items were chosen by accessing a freely available bank of SEL questions, then choosing items that mapped onto social skill domains teachers and students reported as important to them. At the time stakeholders accessed this database, items had been used across several school districts and tested for readability and usability (Crowder, Gordon, Brown, Davidson, & Domitrovich, 2019; Davidson et al., 2018). The bank from which these items were originally retrieved was primarily utilized with 5th–11th grade students (Davidson et al., 2018); therefore, teachers reviewed the items for readability, and the measure was run through an online readability software to ensure that it matched a fourth grade reading level.…”
Section: Methodsmentioning
confidence: 99%